Methanol outbreak in the district of Hulu Langat, 2018 - Zainal Abidin, Muhammad 'Adil; Jalaluddin, Nur Zawani; Abd Halim, Hazariah; Rao, Gunenthira; Habib, Mohd Nasir; Suli, Zaliza (Malaysian Medical Association, 2019)
Introduction: A methanol outbreak occurred in the district of Hulu Langat on 16 September 2018. The Hulu Langat District Health Office received 25 notifications of a suspected methanol poisoning from Kajang and Ampang Hospital. An outbreak investigation was done to determine the source followed by a preventive and control measure. Method: Active case detection was done on cases living quarters and workplaces. Patients were interviewed, and their blood and urine samples were sent for methanol analysis. Samples of suspected alcoholic beverages were also sent for analysis. A suspected case was defined as any person presented with clinical symptoms with a history of consuming alcoholic beverages within five days before symptoms and high anion gap metabolic acidosis. A confirmed case was defined as a suspected case with positive blood and urine methanol. Results: In total, there were 25 suspected cases, of which 12 cases were confirmed. The calculated attack rate was 48%. There were six mortalities (50%) secondary to severe metabolic acidosis. The most common presenting symptom was vomiting (75%) and abdominal pain (41.7%). These cases were linked to consumption of illicitly produced alcohol. Samples of the alcoholic drinks were positive containing high level of methanol. Conclusion: The methanol outbreak in the Hulu Langat was successfully managed. Appropriate control and prevention measures were taken, including health promotion and joint enforcement activities. Steps were taken successfully through collaborations with multiple agencies and cooperation with Selangor Health Departments and the Ministry of Health. Continuous surveillance on the product of liquor, and health promotion are essential to prevent a similar outbreak from happening again in future.